PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MOBIL MEREK AVANZA PADA PT TOYOTA SUMBER HARAPAN DI TANJUNG REDEB - Edwar Ready (Jurnal Ekonomi STIEP, 2022)
The purpose of this study was to find out how much influence brand image has on purchasing decisions for a Toyota Avanza car at PT Toyota Sumber Harapan in Tanjung Redeb. The method used in this study is a simple regression method to see the effect of brand image on purchasing decisions for the Toyota Avanza brand car and using the correlation coefficient to see how much influence the brand image has on purchasing decisions for the Toyota Avanza brand car at PT Toyota Sumber Harapan in Tanjung redeb. Based on the results of the analysis, it is known that the influence of brand image on purchasing decisions for the Toyota Avanza car is classified as strong, judging from the value of r = 0.995. In addition, based on the calculation of the correlation coefficient, it shows the value of r square = 0.989 indicating that 98.9% of the decision to purchase a Toyota Avanza car is influenced by brand image, while the remaining 1.10% is influenced by other factors not examined.